2002
DOI: 10.2134/jeq2002.2470
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Polydimethylsilicone in Biosolids‐Amended Field Plots

Abstract: This research examined the fate of polydimethylsilicones (PDMS) in agricultural test plots amended with municipal biosolids. This 4 yr field study involved addition of 0, 15, and 100 Mg ha(-1) of municipal biosolids, which contained ambient concentrations of PDMS (1272 mg kg(-1) biosolids), to corn and soybean test plots. Soil samples collected at intermittent time intervals were analyzed for soil water, soil organic C, extractable PDMS and PDMS hydrolysis products. Above normal precipitation during the field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Physicochemical properties might serve as broad indicators of OWC behavior once introduced into the environment. However, the landscapes in which biosolids are routinely applied in the United States range from arid to humid and from temperate to subtropical, and the ultimate environmental behavior of any biosolid-derived OWC will be likely be highly dependent on the climate and setting of biosolids application, as has been demonstrated by Traina and others (67).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Physicochemical properties might serve as broad indicators of OWC behavior once introduced into the environment. However, the landscapes in which biosolids are routinely applied in the United States range from arid to humid and from temperate to subtropical, and the ultimate environmental behavior of any biosolid-derived OWC will be likely be highly dependent on the climate and setting of biosolids application, as has been demonstrated by Traina and others (67).…”
Section: Resultsmentioning
confidence: 98%
“…In addition to measuring OWC content in a greater number of biosolids, future research needs to address the transport and behavior of OWCs derived from land application of biosolids under realistic field conditions and in laboratory settings. Extended field studies, such as those by Traina et al (67), provide useful models for future field research in the fate of OWCs. Such research might focus on the processes by which OWCs can be mobilized from biosolid products under the typical condition of their application to soil in agriculture, landscaping, and land-surface remediation.…”
Section: Resultsmentioning
confidence: 99%
“…A model was established predicting the degradation extent of PDMS depending on type of soil and humidity, that is, on climate data such as precipitation and temperature . Finally, in a 4-year field experiment, PDMS loss was monitored after initial dosing with PDMS-containing biosolids . Again, water content in the soil was found to be the limiting factor, precipitation in the course of the study was higher than average, correspondingly the half-life of PDMS under these conditions was rather long, between 2.4 and 3.9 years.…”
Section: Degradation Of Organosiloxanesmentioning
confidence: 99%
“…2,47 Previous studies report that PDMS is hardly to non-biodegradable under aerobic or anaerobic conditions. 2,15,34,100,101 It is suggested that D4 and D5 siloxanes came in wastewaters attached to the AD sludge biosolids (due to their hydrophobicity), and then released to the biogas by volatilisation under mesophilic temperatures. 1,19,46 Other studies hypothesised that D4 and D5 present in the biogas also could come from the resulting products of PDMS hydrolysis as compounds that looked for more stable, less energy-repulsive cyclic structures.…”
Section: Coupled Effects Of Oxygen and Pdms: A Shi Driver Of Bacteri...mentioning
confidence: 99%
“…In addition, PDMS catabolism in the digester will also protect the environment from the siloxanes released through WWTP biosolids. Indeed, studies 15,101 have shown that an important portion of the soils amended with treated AD sludge (biosolids) may be contaminated with organosilicon pollutants, being a potential VOSiCs source and therefore an ecological risk. Above hypotheses must be carefully evaluated in further studies to assess their validity.…”
Section: View Article Onlinementioning
confidence: 99%